Performance Indicators in Young Elite Beach Volleyball Players - Pérez-Turpin, José Antonio; Campos-Gutiérrez, Luis María; Elvira-Aranda, Carlos; Gomis-Gomis, María José; Suárez-Llorca, Concepción; Andreu-Cabrera, Eliseo (Frontiers in Psychology, 2019)
Purpose The aim of this study was to analyze tactical and technical behavior across different ages and genders in young, elite beach volleyball players. Methods Forty teams from the Under-18, Under-20, Under-21, and Under-22 from semifinals and finals of the 2016 World Championships and the 2016 European Championship were analyzed. The sample was composed of 69 sets. The variables studied included: Rally time, set time, match time, serve efficacy (standing serve, floating serve, and jump serve), setting efficacy (forearm, overhand, other, and 2nd attack), attack efficacy, and block efficacy. Student’s t and Mann–Whitney U-tests were used to analyze specific differences between categories. Results Significant differences (p < 0.05) in the pass performance, forearm pass in men (from 78.2 to 49.1%), and overhand pass in men (from 12.2 to 40.45%). In addition, in women forearm pass (from 88.5 to 76.3%) and overhand pass in women (from 1.2 to 9.35%). No significant differences in the effectiveness of attack, rally time, serve, and block efficacy. Conclusion Tactical considerations and gender-specific differences in technical variables may be important for training in young players.